The influence of team psychological safety on team knowledge creation: a study with French and American engineering teams. Issue 6 (24th June 2019) - Cauwelier, Peter; Ribiere, Vincent Michel; Bennet, Alex
Abstract : Purpose: This paper aims to explore the impact of team psychological safety and team learning on the creation of team knowledge. When teams engage in learning, their interactions contribute to improved performance. Very little research evaluates whether the learning also creates new knowledge related to the task or the team itself. Design/methodology/approach: The proposed model is evaluated through a mixed method research design around a team problem-solving experiment. Task- and team-related team mental models are elicited using concept mapping and questionnaires and are measured before and after the experiment. The model is evaluated in engineering teams from the USA and France. Findings: The findings confirm the proposed model; team psychological safety and team learning positively impact team knowledge creation for both task- and team-related knowledge. Originality/value: This research has theoretical, methodological and practical implications. The team psychological safety model is expanded, team learning is evaluated from the team interactions instead of members' self-assessments and team knowledge is measured dynamically. Developing team psychological safety and creating team learning opportunities positively impacts the team's knowledge.